(untitled) (Revista Educação, Artes e Inclusão, 2023)
In this text I present concerns and reflections that emerged in my first teaching practice in artistic education, held in the academic year of 2019/2020 in a public school in Portugal. The work was developed with 05 classes of the curricular component performative arts (theatre), with children from 3 to 9 years old and theoretical foundation mainly from Viola Spolin (2008, 2010) and Augusto Boal (2005). During that school year, the first two months of work were the most difficult. The main challenge was to reconcile what I thought was interesting for students with what they brought, proposed, desired - with who they are. This became my practice: being with ears, heart and sensoriality open to feel how they arrived at each of our meetings and from this perception, to seek for an interaction with them. Often this initiative was “unsuccessful” in the sense that we were unable to produce what would technically be called a class. With the present writing I only organize what was done in order to begin to understand where I am, in the field of the artistic education.